POSTGRADUATE STUDENTS’ ATTITUDE TOWARD STATISTICS PRE AND POST SCENARIO-BASED LEARNING METHOD IN A STATISTICS COURSE - Syed Zamri, Sharifah Norul Akmar; Zulnaidi, Hutkemri; Kwan Eu, Leong (MOJES: Malaysian Online Journal of Educational Sciences, 2020)
Teaching introductory statistics to postgraduate students from multidisciplinary background and with diverse mathematics ability is a huge challenge that many statistics lecturers do not deny. The large ability range can make it very difficult for lecturers to fine tune the right level for effective course delivery. Even though an introductory statistics course has been seen as a necessary component for many postgraduate programs, research has shown that students have come to perceive statistics negatively. One suggestion for improving students’ attitude toward statistics is through the use of innovative instructional approaches. This paper investigates the extent to which scenario-based learning (SBL) method used in a Statistics for Research in Education course were related to improvement in postgraduate students’ attitude toward statistics. Nineteen students who enrolled in the course during the first semester of 2019/2020 were taught using the SBL instructional method. Survey of Attitudes Toward Statistics-36 (SATS-36) was used to measure six statistics attitude components at the beginning and at the end of the course. Overall results show that there is a difference between mean score of attitude before and after exposure to scenario-based learning method. Scenario based learning has some positive effect on student attitude toward statistics.